Amino acid modified copper electrodes for the enhanced selective electroreduction of carbon dioxide towards hydrocarbons. Issue 5 (29th January 2016) - Xie, Ming Shi; Xia, Bao Yu; Li, Yawei; Yan, Ya; Yang, Yanhui; Sun, Qiang; Chan, Siew Hwa; Fisher, Adrian; Wang, Xin
Abstract : Amino acid functionalized Cu nanowire (NW) film electrode exhibits remarkably enhanced selectivity of hydrocarbons during CO2 electroreduction, by stabilizing the key intermediate CHO. Abstract : Electroreduction of carbon dioxide to hydrocarbons has been proposed as a promising way to utilize CO2 and maintain carbon balance in the environment. Copper (Cu) is an effective electrocatalyst for such a purpose. However, the overall selectivity towards hydrocarbons on Cu-based electrodes is still very limited. In this work, we develop a general amino acid modification approach on Cu electrodes for the selective electroreduction of CO2 towards hydrocarbons. A remarkable enhancement in hydrocarbon generation is achieved on these modified copper electrodes, regardless of the morphology of the Cu electrodes. A density functional theory calculation reveals that the key intermediate CHO* is stabilized by interacting with –NH3 + of the adsorbed zwitterionic glycine. Our results suggest that amino acids and their derivatives are promising modifiers in improving the selectivity of hydrocarbons in CO2 electroreduction.